Lesson plan analysis protocol in assessing mathematics and science lessons - Telesphore, Habiyaremye Hashituky; Ntivuguruzwa, Celestin; Ntawiha, Philothere; Agnes, Mbonyiryivuze; Josiane, Mkagihana; Edwin, Byusa; Celine, Byukusenge; Jeannette, Musengimana; Aline, Dorimana; Fidele, Ukobizaba; Kizito, Ndihokubwayo (International Journal of Evaluation and Research in Education (IJERE), 2024)
Lesson planning is important in an educational setting. This study assessed how Rwandan tutors and teachers prepare lesson plans (LPs) before implementing them in a classroom. We employed a current and standard lesson plan analysis protocol (LPAP) developed by researchers from Rwanda to code data. We collected a representative sample of 119 mathematics and science subject lesson plans from teacher training college tutors and secondary school teachers for analysis to serve its usability. The study results revealed that only 11% of collected LPs were teachable as they were rated in both a good (70-79% scores) and very good (80-89% scores) range of LPAP interpretation. It was also found that the special education needs, lesson approaches, and lesson evaluation components got low mean scores (below 50%). These components were not given appropriate attention in developed LPs. Therefore, this study suggests that tutors and teachers build a quality lesson plan based on the standard LPAP.